If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x+5)+2=7x+5(x+2)
We move all terms to the left:
5(x+5)+2-(7x+5(x+2))=0
We multiply parentheses
5x-(7x+5(x+2))+25+2=0
We calculate terms in parentheses: -(7x+5(x+2)), so:We add all the numbers together, and all the variables
7x+5(x+2)
We multiply parentheses
7x+5x+10
We add all the numbers together, and all the variables
12x+10
Back to the equation:
-(12x+10)
5x-(12x+10)+27=0
We get rid of parentheses
5x-12x-10+27=0
We add all the numbers together, and all the variables
-7x+17=0
We move all terms containing x to the left, all other terms to the right
-7x=-17
x=-17/-7
x=2+3/7
| -45+3x)=-30-7x | | 35x=350 | | 19t=16t+12 | | 2y–6–y=y–1 | | -4(5=3x)=-30-7x | | 21x=840 | | 2x-9÷3x+4=-1÷16 | | x+-4/5+6/5=0 | | 15+2x=810-3x | | -17j=3-16j | | 48x=240 | | 100/x=2.75 | | 2x-9/3x+4=-1/16 | | 4.32+4f=6.48 | | F(x)=50^x | | 3=4h-9 | | -4/5+6/5=x | | x-31=2x-98 | | 0.0318=4.4x+0 | | 57=f-134 | | q-131=29 | | 16=9/x^2 | | -15=18k=19k | | 2+4t=4t+2 | | 7g=21 | | 23b-0.25=3.20 | | 6x+12+12-4x=30 | | 9b=8b-14 | | h/4=-9 | | 188-6x^2=32 | | 4j+9=57 | | 81x^2−100=0 |